Degradation of Phenol With A Microwave-Uv Irradiation Treatment System Using NANO-TiO2 - Abha Verma; Venkatesh Meda; Sandeep Badoga; Ajay Dalai (The Global Environmental Engineers, 2017)
The degradation of phenol from various industrial effluents becomes essential and studied in this work. The microwave (MW), ultra-violet (UV) and combination treatment systems were designed and TiO2 nanoparticles were used as photocatalyst for the degradation of 1500ppm phenol in a solution. It was observed that the degradation efficiency was less than 10% in both MW and MW-UV systems without a catalyst. However, the addition of TiO2 particles in MW-UV system has increased the phenol degradation efficiency significantly. The extent of increase in degradation efficiency is dependent on the structural and optical characteristics of TiO2, which is affected by the TiO2 preparation method. In this work, the TiO2 nanoparticles with anatase structure were synthesized by hydrothermal (HT) and sol-gel (SG) methods. The synthesized materials were characterized using X-ray diffraction, FT-IR, thermogravimetric analysis, SEM, high resolution TEM and BET method. The higher degradation efficiency of 24% shown by MW-UV-TiO2 (HT) system in 120 minutes as compared to 20% shown by MW-UV-TiO2 (SG) system could be due to higher surface area and better textural properties of TiO2 prepared by hydrothermal treatment. The effect of various initial concentration of phenol (500-1500ppm) on degradation efficiency of MW-UV-TiO2 (HT) system revealed that the increase in the initial phenol concentration decreased the phenol degradation efficiency.